Research on the efficiency of rocket mine laying under the different wind speed and wind direction - TU Jiangang, WANG Wei, ZHAO Kuisheng, CHEN Shi (Zhihui kongzhi yu fangzhen)
During the operation of rocket mine laying system, due to the influence of wind speed and direction, the landing position of the mine is prone to deviate from the predetermined position after opening the cabin, which leads to the decline of mine laying operation efficiency. In this paper, a model for evaluating the operational efficiency of rocket mine laying bomb is established, the relationship between wind speed and wind direction and the landing position of rocket mine laying bomb is simulated and analyzed. The operational efficiency of rocket mine laying bomb is verified. The simulation results show that the rocket mine laying bomb is affected by crosswind level Ⅳ, and the landing position deviates greatly from the predetermined position. When the longitudinal wind speed reaches level VI, the land position of the rocket mine bomb deviates greatly from the predetermined position. The research results demonstrate the quantitative relationship between the operational efficiency of rocket mine laying bombs and wind speed and direction, which provides methodological support for the rational use of rocket mine laying system in actual combat environment.